2014
DOI: 10.1364/ao.53.005850
|View full text |Cite
|
Sign up to set email alerts
|

Rapid scanning terahertz time-domain magnetospectroscopy with a table-top repetitive pulsed magnet

Abstract: We have performed terahertz time-domain magnetospectroscopy by combining a rapid scanning terahertz time-domain spectrometer based on the electronically coupled optical sampling method with a table-top mini-coil pulsed magnet capable of producing magnetic fields up to 30 T. We demonstrate the capability of this system by measuring coherent cyclotron resonance oscillations in a high-mobility two-dimensional electron gas in GaAs and interference-induced terahertz transmittance modifications in a magnetoplasma in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…1b. To rapidly detect the THz waveform at peak field, we used a TDTS system based on electronically-controlled optical sampling (ECOPS) [30,31], wherein the timing delay between the two ultrafast optical pulse trains that drive the THz emitter and receiver can be electronically modulated very quickly (see Fig. 1c).…”
mentioning
confidence: 99%
“…1b. To rapidly detect the THz waveform at peak field, we used a TDTS system based on electronically-controlled optical sampling (ECOPS) [30,31], wherein the timing delay between the two ultrafast optical pulse trains that drive the THz emitter and receiver can be electronically modulated very quickly (see Fig. 1c).…”
mentioning
confidence: 99%
“…9 There have also been several reports of cyclotron resonance spectrometers being developed that combine pulsed magnetic fields with broadband laser-based terahertz radiation sources. [10][11][12] Laser-based terahertz spectroscopy is a timedomain technique that typically employs slow scanning mechanical delay stages to acquire the terahertz waveforms through combining time-delayed near-infrared and terahertz pulses in a nonlinear medium or photoconductive antenna. The key challenge in utilizing these sources with pulsed magnetic fields has been in developing a detection scheme that can measure the terahertz waveforms within the several millisecond duration of the magnetic field.…”
mentioning
confidence: 99%
“…Approaches to achieving this have included both replacing the slow mechanical delay stage with a fast rotating mirror 10 and using two lasers synchronized with an electronically controlled optical sampling (ECOPS) technique. 12 The ECOPS scheme was the most suitable method for use with short duration magnetic field pulses as Noe II et al 12 showed that it could be used to record four terahertz waveforms during an approximately 14 ms magnetic field pulse.…”
mentioning
confidence: 99%
“…For our magnet system, because of the wait time between magnet shots, on the order of several minutes for shots up to 30 T [22], this method proves to be unreasonably time-consuming for recording the gate signal at many time delays. To date, reported rapid scanning methods for THz-TDS in pulsed magnets include using a rotating delay line for measurements up to 12 T with a 40 T magnet [23], an electronically controlled optical sampling (ECOPS) method up to 2.5 T with a 30 T magnet [24], and, most recently, an asynchronous optical sampling (ASOPS) method up to 13 T with a 31 T magnet [25] to change the relative timing between the pump and gate pulse for each consecutive pair of laser pulses. This leads to a mapping of the pump/probe delay time to the real measurement time.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in Ref. [24], 15 ps of time delay corresponds to 150 µs of measurement time, which provides slightly less than 1% of magnetic field variation at the peak of the magnetic field pulse that varies on a timescale of milliseconds. For shorter-duration magnetic field pulses, for instance µs pulses in a single-turn coil system, required for ultrahigh magnetic field strengths [20], these methods are simply not fast enough, i.e., the magnetic field variation significantly complicates data extraction.…”
Section: Introductionmentioning
confidence: 99%